2008
DOI: 10.1063/1.2907507
|View full text |Cite
|
Sign up to set email alerts
|

Polarized photoluminescence and time-resolved photoluminescence from single CdS nanosheets

Abstract: Articles you may be interested inEnergy transfer from semiconductor nanocrystal monolayers to metal surfaces revealed by time-resolved photoluminescence spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The solid line is a sine function fit, which determines the laser polarization for maximum photocurrent at~17 o with respect to long axis of the nanosheet. For a wurtzite crystal structure, this indicates that the c-axis of this particular nanosheet is almost perpendicular to the long axis of the nanosheet, which is agreement with our previous results predicted by Hoang et al using optical methods [16]. We have done similar measurements on many devices (not shown here) with different atomic orientations, and observed maximum photocurrent for laser polarization parallel to long axis of NS.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The solid line is a sine function fit, which determines the laser polarization for maximum photocurrent at~17 o with respect to long axis of the nanosheet. For a wurtzite crystal structure, this indicates that the c-axis of this particular nanosheet is almost perpendicular to the long axis of the nanosheet, which is agreement with our previous results predicted by Hoang et al using optical methods [16]. We have done similar measurements on many devices (not shown here) with different atomic orientations, and observed maximum photocurrent for laser polarization parallel to long axis of NS.…”
Section: Methodssupporting
confidence: 91%
“…These orientations vary from nanosheet to nanosheet depending upon growth parameters and conditions. In our previous study, these wurtzite structures showed maximum PL emission polarized perpendicular to the caxis of the NS [16,17]. with respect to the long axis of the NS near the reverse bias contact (the most sensitive spot from photocurrent imaging).…”
Section: Methodsmentioning
confidence: 96%
“…16 Using low-temperature polarized PL imaging, we observe high quantum efficiency emission corresponding to A-and B-hole band excitons and, through polarization analysis, we can determine the orientation of the c axis for a particular single CdS nanosheet. 16 Spatially resolved PL imaging of single nanosheets reveals striking PL intensity and line shape variation along the length and width of a nanosheet. This implies some variation in uniformity, strain, or defects across the nanosheet.…”
mentioning
confidence: 99%
“…Other CdS nanosheets, however, were found to have the c axis at other orientations relative to the long axis of the nanosheet. 16 Low temperature PL from a single nanosheet was collected using a 50ϫ / 0.5 numerical aperture long working length microscope objective, which was also used to focus the 458 nm line of a cw Argon ion laser. The PL was dispersed by a triple spectrometer working in subtractive mode, and detected by a 2000ϫ 800 pixel liquid nitrogen-cooled charge-coupled device ͑CCD͒ detector.…”
mentioning
confidence: 99%
“…The waveguiding eigenmodes and lasing from single ZnO nanowires could also be observed by confocal microscopy. [43][44][45] Besides, time-resolved/temperature-dependent micro-photo luminescence is a novel area which will provide new insights and new understanding of the complex dynamic behaviors in single nanostructures [46][47][48] .…”
Section: Scope Of Thesis Workmentioning
confidence: 99%